ArticleSeasonal Incidence of Tobacco Caterpillar, Spodoptera Litura (Fabricius) Infesting Groundnut Crop at Raipur (Chhattisgarh) - Kumar Nayak, Tarun; Deole, Sonali; Shaw, S.S.; Mehta, Nandan (International Journal of Scientific Research in Biological Sciences, 2019)
The field experiment were conducted at Research Cum Instructional Farm at IGKV, Raipur (C.G.) during kharif 2018, to know the seasonal incidence of tobacco caterpillar, Spodoptera litura infesting groundnut. Tobacco caterpillar appeared during 37th standard meteorological week (SMW) with a mean population of 0.24 larva/plant. The peak population were observed in the second week of October with a mean population of 2.28 larva/plant. Thereafter, the population declined gradually and reached to a minimum level of 0.36 larva/plant during 44th SMW i.e. 29th Oct-04November. The correlation between tobacco caterpillar, Spodoptera litura and weather parameters during kharif 2018 results indicated that the population demonstrated a significant negative association with evening relative humidity (r = -0.602), while it showed significant positive association with maximum temperature (r= 0.708) and sunshine hours (r= 0.626). The population of tobacco caterpillar in groundnut had non-significant positive correlation with mean temperature(r= 0.334), while non significant negative correlation with rainfall (r= -0.483), minimum temperature(r= -0.247), morning relative humidity(r= -0.531) and wind velocity(r= -0.414).